Methylene blue confers protection against hepatotoxicity induced by Cisplatin; the involvement of oxidative stress, apoptosis and NCOA4-mediated ferritinophagy - Marawan A. Elbaset; Bassim M. S. A. Mohamed; Passant E. Moustafa; Yosra Assem Hussien; Zeinab A. El-Gendy; Alyaa Farouk Hessin; Mohamed A. Mohamady Hussein; Reda MS Korany; Hany G. Attia; Ashraf Azar; Hany M. Fayed; Bassim (Molecular Biology Reports, 2026)

Neuroprotective Effects of Semaglutide in Cyclophosphamide-Induced Neuropathy: Restoring SIRT1/AMPK, PI3K/AKT/mTOR, and Antioxidant Pathways - Hossein M. Elbadawy; Mohannad A. Almikhlafi; Tahani Saeedi; Mohammed H. Alsubhi; Abdulrahman A. Aljabri; Yosra Assem Hussien; Mevidette Elmadani; Hany M. Fayed; Rehab F. Abdel-Rahman (Journal of Molecular Neuroscience, 2026)

Unveiling phytoconstituents and the anti-inflammatory potential of Crassula tetragona L. in ulcerative colitis: A focus on the PPARγ/SIRT1 axis - Mona A. Raslan; Rehab F. Abdel-Rahman; Hany M. Fayed; Marawan A. Elbaset; Rehab F. Taher (Inflammopharmacology, 2026)
Crassula species are traditionally used and possess anti-inflammatory properties, but Crassula tetragona L. remains largely unexplored. This study intended to characterize C. tetragona aerial parts’ phytoconstituents and assess its anti-ulcerative potential via the PPARγ/SIRT1 pathway. Aerial parts of C. tetragona were extracted using n-hexane (CT1) and 70% aqueous methanol (CT2). Phytoconstituents were profiled by HPLC–ESI–MS/MS (negative ion mode), and phenolics were quantified by MRM-LC–ESI–MS/MS. Column chromatography and NMR were used to separate and identify the compounds. Ulcerative colitis (UC) was induced in rats by intrarectal acetic acid (AA). Animals were assigned into six groups: control group: orally received vehicle for 7 days, UC control group: orally received vehicle for 7 days, and a rectal infusion of 2 mL AA (4% v/v in saline) on the 8th day, 4 treated groups: received CT1 (200 and 400 mg/kg/day), or received CT2 (200 and 400 mg/kg/day), once daily for 7 days by oral gavage and 2 mL AA (4% v/v in saline) on the 8th day. HPLC–ESI–MS/MS identified 66 constituents, including 37 novel compounds, with CT2 exhibiting higher phenolic content. Naringenin, gallic acid, and quercetin were predominant. Five phenolic compounds were isolated from the bioactive extract CT2. Both CT1 and CT2 reduced AA-induced tissue damage, lowered inflammatory markers (calprotectin, CRP, TNF-α, IL-6), improved oxidative stress (reduced MDA, increased GSH, SOD), and upregulated SIRT1 and PPARγ. These results suggest C. tetragona attenuates UC via the SIRT1/PPARγ pathway, indicating its therapeutic potential.

Therapeutic efficacy of canagliflozin against hepatocarcinogenesis induced by CDD/DEN/TAA in a rat model: regulation of AMPK/HIF-1α/YAP-1/TAZ signaling pathways - Hany M. Fayed; Gihan F. Asaad; Marawan A. Elbaset; Ola A. Sharaf; Sawsan S. Mahmoud; Mohamed M. Amin; Zeinab A. El-Gendy; Fatma A. Ibrahim; Sherein S. Abdelgayed; Rehab F. Abdel-Rahman (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Hepatocellular carcinoma (HCC) is the most prevalent type of primary liver cancer. Many medications that had been used for a long period to treat the illness were eventually stopped due to negative effects or the development of drug resistance in HCC patients. Canagliflozin (CANA), a sodium-glucose cotransporter 2 (SGLT2) inhibitor, showed in vitro anti-carcinogenic efficacy against various cancer models’ other livers. The current study used rat models to examine canagliflozin’s therapeutic role against experimentally induced HCC. A total of 32 rats were divided into four groups, eight in each: negative control; HCC control: rats were fed a choline-deficient diet (CDD) and subjected to diethyl nitrosamine and thioacetamide (DEN/TAA) injections for 15 weeks; and treated groups: rats were given CANA (10 and 20 mg/kg b.wt.) orally from the 7th week of the experiment till the end. All the measured markers of HCC, liver function, and inflammatory markers were elevated in the HCC control group compared to the negative control (CTRL). Regarding immunohistochemistry, the HCC group showed downregulation in caspase-3 expression and upregulation in PCNA expression. On the other hand, canagliflozin-treated groups showed dose-dependent improvement in the measured parameters associated with HCC. Moreover, canagliflozin therapy ameliorates the histopathological alterations in HCC-induced rats. Taken together, CANA exhibits anti-HCC effects by activating AMP-activated protein kinase (AMPK) and suppressing the HIF-1α/YAP/TAZ pathway, making it a forthcoming therapeutic option for HCC.